Narratives of recovery after floods: Mental health, institutions, and intervention. (November 2018) - Butler, Catherine; Walker-Springett, Kate; Adger, W. Neil
Abstract: There is increasing evidence that flood events affect the mental health of those experiencing them, with recognition that the period of recovery after the event is particularly important to outcomes. Previous research on flooding has argued that there is a recovery gap that occurs during the long process of recovery at the point when the support provision from public authorities and agencies diminishes, and less well-defined interactions with private actors, such as insurers, begin. This concept highlights the importance of the support and intervention from authorities and other institutions for recovery processes. To date, little research has focused specifically on these relationships and their consequences for people's mental wellbeing through recovery. This study examines the processes of individuals' recovery from flood events, focusing on the role of interaction with agencies in the trajectories of mental health journeys. The analysis applies a narrative approach to in-depth repeated interviews carried out over a fifteen-month period with nine individuals whose homes were inundated by floods in 2013/14 in Somerset, UK. The results suggest strong evidence for institutional support having an important role in how individuals experience their post-flood mental health recovery journeys. The data reveal strategies to maintain psychological and emotional resilience at distinct periods during recovery, and show that both institutional actions and the perceived absence of support in specific circumstances affect the mental health burden of flood events. Highlights: A narrative approach to investigate flood victims' recovery process and well-being. Wellbeing outcomes coevolve with interventions during flood recovery. External support shapes individuals' narratives of post-flood mental health recovery. Institutional actions and perceived absence of support affect mental health burdens. Need for health responses to flood impact will increase with changing climate risks.